Some pharmacokinetic parameters of the trypanocidal drug homidium bromide in Friesian and Boran steers using an enzyme-linked immunosorbent assay (ELISA) - Murilla, G.; Holmes, P.H.; Peregrine, A.S.; Eisler, M.C.; Ndung'u, J.M. (Wiley, 1999)
Pharmacokinetic studies on the trypanocidal drug homidium bromide using a competitive enzyme immunoassay (detection limit 0.1 ng/mL) are reported for non-infected Friesian and Boran steers following treatment with homidium bromide at a dose of 1.0 mg/kg b.w. Following intravenous (i.v.) treatment of Friesian steers (n = 5), the mean serum drug concentrations were 31.9 ± 2.1 and 3.9 ± 0.4 ng/ml at 1 and 24 h, respectively. The decline in serum drug concentration was tri-exponential with half-lives of 0.064 ± 0.037 h for t( 1/2 ?), 7.17 ± 1.87 h for T( 1/2 ?) and 106.3 ± 6.6 h for t( 1/2 ?) for distribution and elimination phases 1 and 2, respectively. Drug was detectable in serum for 17 days following treatment. The mean residence time (MRT) was 63.4 ± 7.5 h. Following intramuscular (i.m.) treatment of Friesian steers (n = 5), the drug concentration at 1 h after treatment was 72.5 ± 2.2 ng/mL. This declined to 9.8 ± 1.8 ng/mL at 24 h. Low concentrations of between 0.1 and 0.3 ng/mL remained in circulation for up to 90 days post-treatment. Following intramuscular treatment of Boran steers (n = 5), the mean serum drug concentration at 1 h after treatment was 112.1 ± 40.3 ng/mL. By 24 h after treatment, the concentration had fallen to 13.0 ± 3.3 ng/mL. Thereafter, the serum drug concentration-versus-time profile and the pharmacokinetic parameters obtained following non-compartmental analysis were similar to those obtained following intramuscular treatment of Friesian steers.